Harvesting visible light with MoO3 nanorods modified by Fe(iii) nanoclusters for effective photocatalytic degradation of organic pollutants. Issue 6 (29th January 2018) - Alam, U.; Kumar, S.; Bahnemann, D.; Koch, J.; Tegenkamp, C.; Muneer, M.
Abstract : Fe(iii ) grafted MoO3 nanorods were prepared by a hydrothermal-cum-impregnation technique. Abstract : The photocatalytic performance of MoO3 is limited due to its weak visible light absorption ability and quick recombination of charge carriers. In the present work, we report the facile synthesis of Fe(iii )-grafted MoO3 nanorods using a hydrothermal method followed by an impregnation technique with the aim of enhancing the light harvesting ability and photocatalytic efficiency of MoO3 . The prepared samples were characterized through the standard analytical techniques of XRD, SEM-EDS, TEM, XPS, UV-Vis-DRS, FT-IR, TG-DTA and PL spectrophotometry. XPS and TEM analyses reveal that Fe(iii ) ions are successfully grafted onto the surface of the MoO3 nanorod with intimate interfacial contact. The photocatalytic performances of the prepared samples were investigated by studying the degradation of methylene blue (MB), rhodamine B (RhB) and 4-nitrophenol (4-NP) under visible light irradiation. The surface-modified MoO3 with Fe(iii ) ions showed excellent photocatalytic activity towards the degradation of the above-mentioned pollutants, where Fe(iii ) ions act as effective cocatalytic sites to produce hydroxyl radicals through multi-electron reduction of oxygen molecules. The improved photocatalytic activity could be ascribed to the effective separation of charge carriers and efficient production of hydroxyl radicals via the rapid capture of electrons by Fe(iii ) through a well-known photoinduced interfacial charge transfer mechanism. Based on scavenger analysis study, a mechanism for the enhanced photocatalytic activity has been discussed and proposed. The concept of surface grafting onto large bandgap semiconductors with ubiquitous elements opens up a new avenue for the development of visible-light-responsive photocatalysts with excellent photocatalytic activity.